2014
DOI: 10.7863/ultra.33.8.1499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of a Modern High‐Definition Head‐Mounted Display in Sonography

Abstract: Because of the remarkably improved image quality and wearability of modern head-mounted displays, a monitoring system using a head-mounted display rather than a fixed-site monitor for sonographic scanning has the potential to improve the diagnostic performance and lessen the examiner's physical burden during a sonographic examination. In a preclinical setting, 2 head-mounted displays, the HMZ-T2 (Sony Corporation, Tokyo, Japan) and the Wrap1200 (Vuzix Corporation, Rochester, NY), were found to be applicable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Head‐mounted displays have been reported to facilitate and expedite processes in the operating room. Starting in 2009, Liu et al . found that anaesthesiologists detected changes in vital signs faster while wearing a head‐mounted display during surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Head‐mounted displays have been reported to facilitate and expedite processes in the operating room. Starting in 2009, Liu et al . found that anaesthesiologists detected changes in vital signs faster while wearing a head‐mounted display during surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, one commercially available modern head-mounted display, the HMZ-T2, provided high-quality images to examiners during sonographic examinations. 20 Therefore, we chose to use the HMZ-T2 display again for this current study. The HMZ-T2 was likewise able to provide patients with high-quality images and acceptable wearability, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported its efficacy in sonography as a viewing screen for the examiner. 20 The high-contrast image quality of modern head-mounted displays confers high diagnostic ability, and it allows the examiner to assume an ergonomically stable posture during sonographic examinations. Because of its compact size, the display is easily introduced and requires no special equipment; thus, patients can also use the display as a personal monitor during sonographic examinations and share diagnostic imaging information with the examiner in real time.…”
mentioning
confidence: 99%
“…We previously showed the clinical application of the HMD in minimally invasive surgeries, transurethral procedures and ultrasonic examinations. [2][3][4][5][6][7] Here, we developed a new distinctive image monitoring system for assistants in da Vinci surgery, by combining to the 3-D endoscope of the da Vinci surgical system ( Fig. 1).…”
mentioning
confidence: 99%